2019
DOI: 10.2196/13698
|View full text |Cite
|
Sign up to set email alerts
|

Using Virtual Reality to Improve Antiretroviral Therapy Adherence in the Treatment of HIV: Open-Label Repeated Measure Study

Abstract: Background Nonadherence to HIV medications is a serious unsolved problem and is a major cause of morbidity and mortality in the HIV-positive population. Although treatment efficacy is high if compliance is greater than 90%, about 40% of people with HIV do not meet this threshold. Objective This study aimed to test a novel approach to improve medication adherence by using a low-cost virtual reality (VR) experience to educate people with HIV about their illness. We hypoth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Study findings showed participant experience resulted in decreased viral load and increased CD4(+). Participants stated the experience was comfortable, educational, and that it would help increase adherence [ 75 ]. VR scenarios can be developed to help increase self-efficacy in discussing STI testing with sexual partners or with a healthcare provider.…”
Section: Resultsmentioning
confidence: 99%
“…Study findings showed participant experience resulted in decreased viral load and increased CD4(+). Participants stated the experience was comfortable, educational, and that it would help increase adherence [ 75 ]. VR scenarios can be developed to help increase self-efficacy in discussing STI testing with sexual partners or with a healthcare provider.…”
Section: Resultsmentioning
confidence: 99%
“… 35 Incorporating interactive elements like gamification and virtual reality technology into IMI can enhance user experiences, facilitate social connections, and improve adherence. 36 …”
Section: Discussionmentioning
confidence: 99%
“…The factors influencing the usability of apps include both usefulness of its information, and its easy manipulation, playfulness 43 , and trustworthiness 44 . The app developed in this study did not include elements that could build trust with the users, elements that could increase interest such as through virtual reality 45 or gamified team-building 46 , and the user experience design process. In addition, another study on self-management app usability among PLWH found that the usability of the app sections differed according to the participants' HIV infection stage 47 .…”
Section: Discussionmentioning
confidence: 99%